GE_GERICHTE C/21183/2013 vom 24. März 2014 - GE Cour de justice (2014)
DÉFAUT DE PAIEMENT; RÉSILIATION ANTICIPÉE; ABUS DE DROIT; EXPULSION DE LOCATAIRE; EXÉCUTION(PROCÉDURE) | CPC.257; CO.257d; CPC.236.3; CPC.337.2; CPC.327.3.B